PARA LANG PO SA TABI: MAKA-PILIPINONG KATANGIAN NG LALABINTAUNIN SA PAGBUBUO NG KÁPWA SA KAPWA PASAHERO NG DYIP (Para lang po sa Tabi: Filipinonize Traits of Teenagers in Building Kápwa with Fellow Jeepney Passengers) - Cabilin, Eldrin Jan; Buquir, Aurora (Social Sciences and Development Review, 2025)
The jeepney is hailed as the "king of the road." This monarch of the streets is often adorned with vibrant colors, intricate decorations, and an extravagant design. Though an unseen part of our daily lives yet, it carries profound cultural significance symbolizing our Filipino identity. Within the jeepney the Filipino value of pakikipagkapwa is strongly manifested as the heart or most important among our Filipino values according to Virgilio Enriquez from the perspective of Sikolohiyang Pilipino. This study sought to explore how the concept of kapwa is formed among passengers who interact daily within this shared space. Employing the indigenous Filipino research methods of pagtatanong-tanong and pakikipagkuwentuhan by Javier, narratives were gathered and analyzed from ten lalabintaunin (adolescents). These narratives were interpreted using Enriquez's Antasan ng Pagtutunguhan to provide a clear and in-depth discussion of how the concept of kapwa is developed. The study identified the following positive Filipino traits that emerge from this sense of shared identity among jeepney passengers: a. bayad po; b. pára po sa tabi; c. tinginan at pakiramdaman; d. kuwentuhan; e. limos at malasakit; and f. punuan at bigayan. On the other hand, certain negative Filipino traits among passengers also surfaced such as: a. pagwawalang bahala o walang pakialam;  b. pagkagalit at pagdadabog;  c.  tsismisan;  d. siksikan at singitan;  e. budol;  f.  lamangan; and g. pakutuban.
Keywords: jeepney; kápwa; lalabintaunin; Filipino traits; passengers; Filipino Psychology